2016
DOI: 10.17221/185/2016-pse
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of <sup>15</sup>N-nitrogen in fertilization of pea mixtures with wheat, barley, and oats

Abstract: The effect of mineral nitrogen (N) nutrition on seed production and acquisition of 15 N from fertilizers by components of cereal-pea mixtures was investigated. Yields of wheat-pea and oats-pea mixtures raised together with the increase of cereals percentage in the pot, and higher seed yields of mixture with barley was affected by a larger share of pea plants. The percentage of nitrogen derived from fertilizers was significantly higher in cereals as compared with pea. Pea accumulated the greatest quantity of ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…It should be noted that the N-utilization coefficient for winter wheat for the white lupin residues was 59.0% in the control and 61.9% in the N-fertilized subplots (Table 4). These results are similar to other studies, e.g., according to Rutkowska and Pikuła [26], the percentage of N derived from fertilizers was significantly greater in wheat (56%) compared to field pea (15-17%).…”
Section: High Content Of Nosupporting
confidence: 92%
“…It should be noted that the N-utilization coefficient for winter wheat for the white lupin residues was 59.0% in the control and 61.9% in the N-fertilized subplots (Table 4). These results are similar to other studies, e.g., according to Rutkowska and Pikuła [26], the percentage of N derived from fertilizers was significantly greater in wheat (56%) compared to field pea (15-17%).…”
Section: High Content Of Nosupporting
confidence: 92%
“…The influence of the fertilizer N timing can also be understood from the higher NDFS contribution in the early N application groups. The NDFS commonly overcame the NDFF contribution in cultivated crops [ 44 , 52 ]. However, increased contribution of NDFS has often accompanied by more N asynchrony [ 13 , 42 , 53 ], as well as in the N-OATS and N-PLANT groups.…”
Section: Discussionmentioning
confidence: 99%
“…The yield was higher for mixtures harvested at the stage of flat green pod of field pea. Also studies by Staniak et al (2012), Bojarczuk et al (2014) and Rutkowska and Pikuła (2016) revealed that legume/cereal mixtures harvested at a later growth stage produced more biomass.…”
Section: Discussionmentioning
confidence: 90%
“…Spring cereals use roots to penetrate the surface soil layer whereas legumes reach the deeper layer. Also, plant species have different periods of critical demand for water and nutrients (Rutkowska and Pikuła, 2016).…”
Section: Introductionmentioning
confidence: 99%